Social Networks: Reason, Freedom, Existence - Elía-Mañú, Oscar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In the first quarter of the 21st century, social networks are subject of disillusionment. Like the rest of TICS, the hopes placed in them in relation to reason, deliberation and democracy seem to have been shattered. Nor does the other pole of modernity, freedom, seem to be satisfied with social nethworks. Heidegger and his approach to technology provides the metaphysical key to understanding the essence of social networks, and points out a way of access that is an ontological interpretation in a realist key, of which three of the fundamental aspects will be outlined.